THE INFLUENCE OF COMMUNITY PARTICIPATION, TRANSPARENCY, ACCOUNTABILITY, AND THE ROLE OF VILLAGE OFFICIALS ON VILLAGE REVENUE AND EXPENDITURE BUDGET MANAGEMENT (APB Desa) (Case Study in Villages in Sawit District, Boyolali Regency) - Sari, Anisa Arum; Dewi, Maya Widyana; Rukmini, Rukmini (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This study seeks to investigate how community involvement, transparency, accountability, and the function of village officers affect the management of village revenue and expenditure budgets in villages across the Boyolali Regency's Sawit District. This investigation employs a quantitative data analysis approach with testing utilizing the Multiple Linear Regression Model. In this study, Village Heads, Village Officials, and Village Consultative Bodies (as community representatives) in villages across the Sawit District, Boyolali Regency, were the populations used. The research sample of 86 individuals was selected using purposive sampling in this study. The findings of this research show that in villages across the Boyolali Regency's Sawit District, the Management of Village Revenue and Expenditure Budgets (APB Desa) is significantly impacted by partial community involvement, transparency, accountability, and the function of village officials.